2016
DOI: 10.1177/1065912916639138
|View full text |Cite
|
Sign up to set email alerts
|

Who Supports Populism and What Attracts People to It?

Abstract: In this paper, we engage with the emerging literature that studies the support for populism by means of attitudes among the public at large. More specifically, our paper has two objectives. First, we extend recent research by Akkerman et al. by showing that their measure performs rather well in a context that differs from the one it was originally formulated in. Data from Flanders (the Dutch speaking part of Belgium, N = 1,577) also demonstrate that the support for populism can be empirically distinguished fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
288
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 417 publications
(354 citation statements)
references
References 42 publications
(56 reference statements)
16
288
1
13
Order By: Relevance
“…with the programmes of the parties and the discourses of the leaders (see Hawkins 2009;Rooduijn 2013). However, recent research has also identified populist attitudes among voters Hawkins et al 2012;Spruyt et al 2016). The distinction between elites and the people and the notion that sovereignty should lie not with the elites but with the people are also found among the supporters of populist parties.…”
mentioning
confidence: 99%
“…with the programmes of the parties and the discourses of the leaders (see Hawkins 2009;Rooduijn 2013). However, recent research has also identified populist attitudes among voters Hawkins et al 2012;Spruyt et al 2016). The distinction between elites and the people and the notion that sovereignty should lie not with the elites but with the people are also found among the supporters of populist parties.…”
mentioning
confidence: 99%
“…Substantial susceptibility to populist arguments also results from the growing inequalities and uncontrolled actions of owners of supranational capital which is poorly controlled by the national elites [15]. The dissemination of information and ideas incompatible with the conventional way of thinking is frightening to citizens.…”
Section: Why There Is Susceptibility To Populist Arguments?mentioning
confidence: 99%
“…• The leader along with his closest collaborators formulate a specific populist program of social change (political, electoral program) [14,15].…”
Section: Repeating Sequence Of Eventsmentioning
confidence: 99%
“…Mudde, 2010;Kriesi, 2014;Spruyt et al, 2016). Eribon (2013) and others have suggested that by voting for populist parties, the modern precariat aims to defend their collective identity.…”
Section: Third Modernity and Practices Of Simulationmentioning
confidence: 99%
“…In respect of modernization theory, populist movements are commonly conceptualized as an explicitly anti-modernist phenomenon, specific to the contemporary era of 'regressive modernity' (Inglehart and Norris, 2017; see also Geiselberger, 2017) and typically mobilizing the losers of modernization (Oliver and Rahn, 2016;Spruyt et al, 2016). From this perspective, the proliferation of populism then appears either as a response to rising levels of economic inequality as described by Piketty (2014) and Milanovic (2016), or as a 'cultural backlash' by social strata that have not moved along with the modernization-induced shift towards cosmopolitan liberal value orientations (Inglehart and Norris, 2016).…”
Section: Towards a Shift Of Perspectivementioning
confidence: 99%